David Tracy on fragments, fragmentation, and frag-events: On picking up a conversation - Conradie, Ernst (Stellenbosch Theological Journal, 2021)
This contribution offers a review of David Tracy's recent collection of essays entitled Fragments: The Existential Situation of Our Time (2020). This volume is quite an event since Tracy's last monograph was published in 1994. This review gives an account of the continuity and discontinuity in Tracy's oeuvre with reference to themes such as conversation, fragments, the Infinite, and an analogical imagination. It also mentions some other jewels found in Fragments by picking up on a conversation with Tracy that started with the author's doctoral thesis on Tracy, completed in 1992.